Global Association between Thermophilicity and Vancomycin Susceptibility in Bacteria - Roy, Chayan; Alam, Masrure; Mandal, Subhrangshu; Haldar, Prabir K.; Bhattacharya, Sabyasachi; Mukherjee, Trinetra; Roy, Rimi; Rameez, Moidu J.; Misra, Anup K.; Chakraborty, Ranadhir; Nanda, Ashish K.; Mukhopadhyay, Subhra K.; et al. (Frontiers in Microbiology, 2016)
Exploration of the aquatic microbiota of several circum-neutral (6.0-8.5 pH) mid-temperature (55-85 OC) springs revealed rich diversities of phylogenetic relatives of mesophilic bacteria, which surpassed the diversity of the truly-thermophilic taxa. To gain insight into the potentially-thermophilic adaptations of the phylogenetic relatives of Gram-negative mesophilic bacteria detected in culture-independent investigations we attempted pure-culture isolation by supplementing the enrichment media with 50 µg ml-1 vancomycin. Surprisingly, this Gram-positive-specific antibiotic eliminated the entire culturable-diversity of chemoorganotrophic and sulfur-chemolithotrophic bacteria present in the tested hot water inocula. Moreover, it also killed all the Gram-negative hot-spring isolates that were obtained in vancomycin-free media. Concurrent literature search for the description of Gram-negative thermophilic bacteria revealed that at least 16 of them were reportedly vancomycin-susceptible. While these data suggested that vancomycin-susceptibility could be a global trait of thermophilic bacteria (irrespective of their taxonomy, biogeography and Gram-character), MALDI Mass Spectroscopy of the peptidoglycans of a few Gram-negative thermophilic bacteria revealed that tandem alanines were present in the fourth and fifth positions of their muropeptide precursors (MPPs). Subsequent phylogenetic analyses revealed a close affinity between the D-alanine-D-alanine ligases (Ddl) of taxonomically-diverse Gram-negative thermophiles and the thermostable Ddl protein of Thermotoga maritima, which is well-known for its high specificity for alanine over other amino acids. The Ddl tree further illustrated a divergence between the homologs of Gram-negative thermophiles and mesophiles, which broadly coincided with vancomycin-susceptibility and vancomycin-resistance respectively. It was thus hypothesized that thermophilic Ddls have been evolutionarily selected to favor a D-ala-D-ala bonding. However, preference for D-ala-D-ala-terminated MPPs does not guarantee vancomycin susceptibility of thermophilic bacteria as the large and relatively-hydrophilic vancomycin molecule has to cross the outer membrane before it can inhibit peptidoglycan biosynthesis. Literature shows that many mesophilic Gram-negative bacteria also have D-ala-D-ala-terminated MPPs, but they still remain resistant to vancomycin due to the relative impermeability of their membranes. But the global vancomycin-susceptibility phenotype of thermophilic bacteria itself testifies that the drug crosses the membrane in all these cases. As a corollary, it seems quite likely that the outer membranes of thermophilic bacteria have some yet-unknown characteristic feature(s) that invariably ensures the entry of vancomycin.